Characterisation of phenotypic and genotypic resistance to new and re-purposed tuberculosis drugs in the Western Cape, South Africa - Auma, Erick Otieno (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.